Orange-Canadian Unionists and the Irish Home Rule Crisis, 1912-1914 - McLaughlin, Robert (Ontario History, 2006)
In April 1912, the third Irish Home Rule Bill was introduced in the British House of Commons. The north of Ireland erupted with protests opposing Home Rule for Ireland, claiming it would mean “Rome Rule.” Ulster Protestants were particularly opposed to Irish Home Rule and made certain that its implementation would fail. Orange Canadians were interested in events in Ireland to such an extent many became active participants in those events, through moral, material, and even physical support of the Ulster unionist opposition to the implementation of Irish Home Rule. This Orange Canadian response and demonstration of fidelity with their Irish co-religionists is often overlooked by historians of the Canadian Order. Canadian Orangemen maintained strong connections with their brethren in Ireland, and viewed themselves as a North-American counterweight to the strong support Irish nationalists found in the United States. These determined expressions of support for the stance taken by their Orange brethren in Ireland continued over such a long period of time, and were demonstrated with such intensity, that these expressions of fidelity and support to Irish Protestants generally should not be viewed as a fleeting chant, or as anachronistic, but should be viewed in the larger context of transnational Orange solidarity and brotherhood.